Research of kinematic characteristics of basic attacking technical action young wrestlers freestyle - W.W. Yaremenko (Physical Education of Students)
Purpose . Іdentified temporal characteristic structures basic attacking technicians action young wrestlers freestyle different qualifications. Material . The study involved 38 boys engaged in freestyle wrestling. Held analysis specially scientifically literature evidenced about that exists objective necessity at decisions question concerning study biomechanical speciality technicians wrestlers freestyle for working technology formation sports technicians athlete during pre-basic training. Results . Identified biomechanical characteristics defined kinematic structure of the temporal and spatial-temporal characteristics of the basic techniques. Shown variability of the individual phases of the basic techniques. Conclusions . Research duration preparatory, basic and final phases basic attacking technical action at stand young wrestlers freestyle different qualifications testifies about her variability and ambiguous at each studied technical action.